(untitled) (Research, Society and Development, 2021)
Introduction: The influence of biological rhythmicity on the regulation of several systems, including the gastrointestinal system, is well known. In this context, several recent studies relate the release of melatonin, as an important substance in the healing of ulcerative lesions in the gastrointestinal tract. Objective: To investigate studies and evidence about the role of melatonin as a complementary treatment for gastroduodenal ulcers and its relationship with chronobiology. Methodology: This is an integrative review study, carried out through an active search in the Scientific Eletronic Library Online (SciELO), PubMed, Science Direct and Latin American and Caribbean Literature in Health Sciences (LILACS) databases in August 2020. Results: In several of the studies analyzed, the administration of melatonin proved to be effective and safe to accelerate the rate of healing of gastroduodenal ulcers of different etiologies due to its antioxidant and anti-inflammatory activities. Conclusion: Although there is innumerable evidence, the literature is still scarce regarding the treatment or pre-treatment of ulcers with melatonin, either alone or in conjunction with other drugs.